Alterations of Epidermal Cells Functional Activity in Fish Due to Infection - Päkk, Priit (Eesti Maaülikool, 2012)
Previous results have suggested that epidermal club cells have a generic role in response to injury and that they display intense phagocytic activity, having an anti-parasitic function in the host. The presently reported doctoral theses focused on the alterations of epidermal club cell activity and on the integration with mucous cells in common carp epidermis by ichthyophthiriosis and mucus production in triploid Atlantic salmon by gyrodactylosis also elucidate processes involved in epidermal papillomatosis regeneration of koi carp which occurs during a steady temperature increase. The results of this thesis demonstrate the potential role of club cells in healing process during and after damages in carp, but not anti-parasite functions of these cells. For better understanding of club and mucous cells integrated functions further studies should conduct more extensive sampling from all parts of the freshwater fish. Mõnedel kalaliikidel asuvad epidermise ogakihis suured, ühe või kahetuumalised eosinofiilsed nuirakud, millede mõõtmed ulatuvad 40 μm. Viimased avaldatud uuringud näitavad, et nuirakkudel võib olla teatud roll epidermise struktuuri ennistumisel ja tervenemisel pärast vigastusi ning nad omavad teatud mõju sellesse tunginud välisparasiitidesse. Doktoritöö eesmärgiks oli, kasutades histoloogia ja histokeemia meetodeid, selgitada haigustekitajate poolt põhjustatud rakulise struktuuri ja aktiivsuse muutusi kalade epidermises. Doktoritöös avaldatud uuringute tulemused näitavad, et nuirakud täidavad olulist rolli epidermise tervenemisel ja seda, et need asendavad ogakihis prolifereerumise lõpetanud, välispinnale suundunud ja seal avanenud limarakke, kuid ei oma antiparasiitseid omadusi per se. The publication of this dissertation is granted by the Graduate School in Biomedicine and Biotechnology.